ANALISIS KEPEMILIKAN MANAJERIAL DAN KINERJA KEUANGAN PERUSAHAAN SEBELUM DAN SETELAH MERGER - Ismanto, Deny (Fakultas Ekonomi dan Bisnis Universitas Ahmad Dahlan, 2015)
The purpose of this research is to find any changes managerial and financial performance of the company before and after a merger. Managerial kepemilkan measured by the number of managerial compared with the number of shares outstanding. Measured by the number of managerial ownership managerial compared with the number of shares outstanding. Then to the company financial ratios are measured with a total assets and turnover net profit margin, and return on assets. The analysis was conducted using one sample t-test and paired sample test. Based on different paired test sample test May be known that the significance of tailed 0,286 (2) on the level of trust 95 %. Because probability significance (0,286) larger than 0.05 then can conclude that there is no difference between managerial possession before and after the merger. Based on test different t-test can be seen that the significance of the total turnover (0,085) assets, net profit margin (0,362), and return on assets (0,531) 95 percent in the level of trust. Greater significance because the probability of 0.05 it can be concluded that there is no difference between the company financial performance before and after a merger.